2019
DOI: 10.3390/en12214055
|View full text |Cite
|
Sign up to set email alerts
|

Hour-Ahead Solar Irradiance Forecasting Using Multivariate Gated Recurrent Units

Abstract: Variation in solar irradiance causes power generation fluctuations in solar power plants. Power grid operators need accurate irradiance forecasts to manage this variability. Many factors affect irradiance, including the time of year, weather and time of day. Cloud cover is one of the most important variables that affects solar power generation, but is also characterized by a high degree of variability and uncertainty. Deep learning methods have the ability to learn long-term dependencies within sequential data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(34 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Other future research aiming to improve the forecast model's ability to learn nonlinear complexities with regards to cloud coverage and seasonal variations may consider the use of patch-based samples from the satellite images to analyze a broader geographic area for more context on nearby atmospheric and meteorological conditions. The drawback however is that patch-based approaches can be time-consuming and more complex, which may require more sophisticated forecast models such as CNN models [1,35], long short-term memory networks [9], and gated recurrent unit-based models [16]. While this study focuses on integrating COMS and H8 satellite image data, future works can include different ancillary data such as solar resources and various meteorological factors related to the atmosphere and local climate to produce a more comprehensive input dataset which would be more representative of local conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other future research aiming to improve the forecast model's ability to learn nonlinear complexities with regards to cloud coverage and seasonal variations may consider the use of patch-based samples from the satellite images to analyze a broader geographic area for more context on nearby atmospheric and meteorological conditions. The drawback however is that patch-based approaches can be time-consuming and more complex, which may require more sophisticated forecast models such as CNN models [1,35], long short-term memory networks [9], and gated recurrent unit-based models [16]. While this study focuses on integrating COMS and H8 satellite image data, future works can include different ancillary data such as solar resources and various meteorological factors related to the atmosphere and local climate to produce a more comprehensive input dataset which would be more representative of local conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For market participants, PV forecasts are required to avoid potential penalties and generate precise bids. In Korea, the PV market has experienced remarkable growth over the past decade due to considerable improvements in domestic PV technology, steady funding for PV research, implementation of government policies promoting the use of renewable energy, and the establishment of basic plans and detailed action programs [14][15][16]. As shown in Figure 1, the PV power market is continuously expanding in PV power transactions and PV power consumption.…”
Section: Introduction To Meteorological Satellites For Photovoltaic Pmentioning
confidence: 99%
“…The commonly employed statistical measures for solar resource forecasting applications include RMSE, MAE and MAPE [29,30,55]. The accurate forecasting of solar irradiance is an intricate process due to the stochastic and intermittent nature of the solar irradiance [28,56]. The solar irradiance is only present during the daytime, whereas it has a very low or zero value during the night.…”
Section: E Statistical Measuresmentioning
confidence: 99%
“…The final forecasting result is based on summing the forecast of each learner [18]. DLMs comprising LSTM neural network and gated recurrent unit neural network also presented superior results in forecasting solar irradiance, compared to the other MLMs [26][27][28]. Qing et al [26] utilized the LSTM model for hourly day-ahead forecasting of solar irradiance.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also concluded that GRU is less resource-intensive and faster compared to LSTM. The proposed work builds on our prior work [28], where we analyzed the performance of LSTM and GRU for GHI forecasting with and without using exogenous variables for one hour ahead forecasting [29]. Our observation in our prior work is that including weather variables particularly cloud cover significantly improved forecasting performance for both LSTM and GRU compared to univariate models.…”
Section: Introductionmentioning
confidence: 99%